The Role of Corporate Reputation & Distinctive Organization Capability in Developing Business Model Innovation: Case study of Indonesia ICT Firm in Facing Industry Resolution 4.0 - WW Mihardjo, Leonardus; ., Elidjen; Alamsjah, Firdaus; ., Sasmoko (International Journal of Engineering and Technology, 2019)
Business model innovation is key important in facing industry 4.0 where the digital technology through internet and mobile influences the life style of people. Our paper has objectives to provide the antecedents of Business model innovation and to compare the impact between corporate reputation and distinctive organizational capability in developing business model innovation. The study is based on digital disruption phenomenon, where established companies are disrupted the new business model by new entrance through leveraging digital capability. The study is focusing on Information, Communication and Technology (ICT) incumbent companies in developing business model innovation as the second curve to sustain their business. ICT industry is the important sector to enable the development in other industry and has significant influence in economic growth. Currently, the higher economy growth relies on the emerging market such as Indonesia. Indonesia ICT market has unique characteristics where the innovation has grown rapidly but the infrastructure lacked behind and also the market was very competitive. Hence, there was the gap between the opportunity in innovation and the development of digital infrastructure, and for incumbent firm was the mitigation of investment risk of the ICT infrastructure and compete with new entrance that bring new business model and market. The Incumbent has the advantage of the corporate reputation and required to develop the new capability in providing the distinctive capability. However, the study of developing business model innovation for incumbent firm in market focus on corporate reputation has limited. The study is done through empirical research using 35 samples of Indonesia ICT firm. The analytical approach and the solution technique used Smart Partial Least Square (PLS). The Research finding shows that the distinctive organization capability has significant influence compare with the corporate reputation in developing business model innovation. The study has the implication that in theory, in developing business model innovation focus on distinctive organization capabilities rather that rely on corporate reputation. It means the ICT Incumbents firms are required to transform their capability align with market change. For managerial management, this study has implication the urgency in developing distinctive organizational capability in respective units, especially in intangible asset.Â Â  Further research can be enhanced by expanding the research sample and industry, and also can be expanded into longitudinal study as part of transformational model for incumbent firms.Â